Managing Culture: Reflecting on Exchange in Global Times eds. Victoria Durrer and Raphaela Henze (Palgrave Macmillan, 2020). - Montgomery, Andrea (Irish Journal of Arts Management and Cultural Policy, 2021)
Review of a collection of essays on intercultural best practice in global arts and education policy and management with real-world case studies. Managing Culture reflects on the damaging power dynamics at play across global culture and seeks to gather critical analysis and case studies from across the globe to address issues under the headings of Conditions, Practice, Education and Future Direction. Rich with useful examples and analysis the book manages to both educate the reader and provide examples for constructive change.